The Fabrication of a Gellan Gum-Based Hydrogel Loaded With Magnesium Ions for the Synergistic Promotion of Skin Wound Healing - Li, Wenqiang; Jian, Xingling; Zou, Yanfen; Wu, Lin; Huang, Haiyan; Li, Hui; Hu, Dandan; Yu, Bo (Frontiers in Bioengineering and Biotechnology, 2021)
To accelerate serious skin burn wound healing in a convenient manner, an interpenetrating network of hydrogel consisting of gellan gum and polyacrylamide was synthesized by chemical crosslinking and Mg2+ ion immersion techniques. The prepared Mg2+@PAM/GG hydrogel was characterized by morphology, water vapor loss, swelling ratio, rheological properties, tensile mechanical, biocompatibility, and flow cytometry study. The results show that Mg2+@PAM/GG hydrogel’s mechanical strength could be enhanced by the dual network structure and physical crosslinking agent Mg2+ ions. In addition, the tension strength of Mg2+@PAM/GG hydrogel is obviously increased from 86 to 392 kPa, the elongation at break increased from 84 to 231%, and crosslinking density N increased from 4.3 to 7.2 mol/m3 compared with pure GG hydrogel. The cumulative release curve of Mg2+ ions shows that the multiple release mechanism of Mg2+ ions belong to non-Fick’s diffusion. Meanwhile, in vitro experiments show that Mg2+@PAM/GG double network hydrogel has favorable proliferation and an NF-κB pathway inhibition property for fibroblast cells. Finally, the healing effect of the Mg2+@PAM/GG was evaluated in a rat full-thickness burn model. The animal study demonstrates that Mg2+@PAM/GG could accelerate the healing efficiency in case of the sustained-released Mg2+ ions in wound beds. Considering this excellent performance, this convenient prepared hydrogel has great potential as a commercial application for skin full-thickness burn healing materials.